High Performance Interconnect Network for Tianhe System - 廖湘科 庞征 王克非 卢宇彤 谢旻 夏军 董德尊 所光 (Journal of computer science and technology, 2015)
In this paper, we present the Tianhe-2 interconnect network and message passing services. We describe the architecture of the router and network interface chips, and highlight a set of hardware and software features effectively supporting high performance communications, ranging over remote direct memory access, collective optimization, hardwareenable reliable end-to-end communication, user-level message passing services, etc. Measured hardware performance results are also presented.